Oxygen Partial Pressure Impact on Characteristics of Indium Titanium Zinc Oxide Thin Film Transistor Fabricated via RF Sputtering - Ming-Hung Hsu; Sheng-Po Chang; Shoou-Jinn Chang; Wei-Ting Wu; Jyun-Yi Li (Nanomaterials, 2017)
Indium titanium zinc oxide (InTiZnO) as the channel layer in thin film transistor (TFT) grown by RF sputtering system is proposed in this work. Optical and electrical properties were investigated. By changing the oxygen flow ratio, we can suppress excess and undesirable oxygen-related defects to some extent, making it possible to fabricate the optimized device. XPS patterns for O 1s of InTiZnO thin films indicated that the amount of oxygen vacancy was apparently declined with the increasing oxygen flow ratio. The fabricated TFTs showed a threshold voltage of −0.9 V, mobility of 0.884 cm2/Vs, on-off ratio of 5.5 × 105, and subthreshold swing of 0.41 V/dec.